Modern manifestations of death in two literary works - Hend Alsudairy, T (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2012)
This paper relates to the concept of death as presented in two works of literature. The major theme in both works is death but the perspective is different, if not contradictory. James Cary’s Red Letter Day presents the innocent child’s perception of death as something mysterious and apprehensive while in Tuesdays with Morrie, death appears to be a dynamic power, demonstrating how the old professor gives his best to humanity. The paper will discuss the religious aspect of death and people's fear of death, its causes and results on people's life.